DO WOMEN IN RURAL AREAS STILL PREFER HOMEBIRTH WITH TRADITIONAL BIRTH ATTENDANTS? A QUALITATIVE STUDY OF WOMEN IN RURAL AREA OF KUTAI KERTANEGARA EAST KALIMANTAN - Annisa Nurrachmawati; Moh. Hakimi; Adi Utarini (Public Health of Indonesia)
Background: There continues to be a gap between facility-based delivery and homebirth. This condition is influenced by various social and cultural factors, which in rural areas could affect childbirth in health facilities.